Adult entero-enteric intussusception caused by small bowel submucosal lipoma - Karel Borroto Martínez; Raysy Sardiñas Ponce; Yoanna Ramírez Fernández; Mónica Galindo Estévez (Revista Cubana de Medicina Militar, 2023)
Introduction: Intussusception is the prolapse of one gastrointestinal segment into an adjacent part. Its incidence in adults is less than 10%. Objective: To presents a case of adult entero-enteric intussusception caused by small bowel submucosal lipoma. Clinical case: A 66-year-old male patient with vague clinical manifestation that presented in a computed tomography scan typical invagination image, it showed the classical "target" and "sausage-like" images. He underwent surgery, where the diagnosis of adult entero-enteric intussusception was confirmed and then an en-bloc resection was performed. Anatomopathological examination revealed a submucosal lipoma of the jejunum. Gastrointestinal lipomas have an incidence of 0.035% - 4.4%. Conclusion: This is a rare case, not only because the intussusception is uncommon in adults but for the lead point found in it.